IMPLEMENTASI PENDEKATAN PROBLEM SOLVING DALAM PENCAPAIAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SERTA HABITS OF MIND SISWA MTs - Ramlah Ramlah; Rippi Maya (Universitas Sultan Ageng Tirtayasa, 2018)
ABSTRACTThis study aims to examine the implementation of problem solving approach in achieving the ability of creative thinking and students' habits of mind. This quasi-experimental study took all of students in one private of MTs in Purwasari-Karawang as population. Two classes of experiment class (problem solving approach) were selected for 28 students, and control class (conventional learning) of 30 students. Quantitative data analysis uses SPSS 17 for windows. The results showed that the the implementation of mathematics learning process with problem solving approach is quite effective.The achievement of students' mathematical creative thinking ability using problem solving approach is not better than students who use conventional learning. There is no difference in the ability of mathematical creative thinking as well as students' thinking habits in both learning groups.Keyword: Problem Solving approach, The Ability of Creative Thinking Mathematically, and Habits of Mind